Buccal dental-microwear and feeding ecology of Early Pleistocene Theropithecus oswaldi from Cueva Victoria (Spain). Issue 142 (May 2020) - Martínez, L.M.; Estebaranz-Sánchez, F.; Ferràndez-Cañadell, C.; Romero, A.; Ribot, F.; Galbany, J.; Gibert, L.; Pérez-Pérez, A.
Abstract: Despite the scarcity of fossil specimens of Theropithecus oswaldi in Eurasia, its presence out of Africa attests to the great dispersal of this Papionini genus during the Early Pleistocene. In the present study, we analyze the buccal dental microwear of T. oswaldi ( T. o. leakeyi ) fossil specimens from Cueva Victoria (Southeastern Spain). This analysis is the first characterization of the feeding ecology of T. oswaldi in Europe. The buccal microwear pattern of the molar and premolar teeth of T. oswaldi from Cueva Victoria shows great similarities to that observed for the extant frugivorous forest-dwelling Mandrillus sphinx and mangabeys ( Cercocebus sp.)—both species adapted to durophagous dietary habits—while significantly different from that observed for the gramnivorous Theropithecus gelada . These results suggest that T. oswaldi from Cueva Victoria could have exploited both hard-shelled fruits or seeds and succulent fruits from open and forested Mediterranean ecosystems.